The management of a duodenal fistula involving the right hepatic duct: a rare case report - Ming, Qiu; Jun, Yang; Nai-wen, Luo; Lei, Cao; Yu-dong, Fan; Shu-guang, Wang (Frontiers in Medicine, 2024)
The formation of an internal fistula between the biliary system and the gastrointestinal tract is a rare condition with various etiologies, predominantly associated with recurrent chronic inflammation of the biliary system and tumors. Patients with this condition may lack specific clinical manifestations, presenting with symptoms such as abdominal pain, fever, jaundice, or may show no clinical signs at all. Common types of internal fistulas include cholecystoduodenal fistula, cholecystocolonic fistula, and choledochoduodenal fistula. Among these, the right hepaticoduodenal fistula is extremely rare and seldom reported in clinical literature. We herein report a case of right hepaticoduodenal fistula and analyze its mechanism, treatment principles, and preventive measures through a literature review.A 67-year-old male patient presented with intermittent epigastric pain persisting for a decade. Throughout this period, there were no signs of fever or jaundice. He was admitted to our hospital following an abdominal CT scan indicating right intrahepatic bile duct dilatation and presence of gas within it. Twelve years earlier, he had been diagnosed with gallbladder stones, underwent open cholecystectomy at an external hospital, and was discharged post-surgery without complications. His personal, marital, and family medical history were unremarkable. On physical examination, his